Integrating boron atoms into ultrathin organic polymer for visible light photocatalytic CO2 reduction to CH4 with nearly 100% selectivity. Issue 10 (14th February 2022) - Hou, Linquan; Tang, Guoen; Huang, Hao; Yin, Shiheng; Long, Bei; Ali, Atif; Deng, Guo-Jun; Song, Ting
Abstract : A facile way to fabricate an ultrathin organic polymer with B as the active site for nearly 100% selective CO2 -to-CH4 conversion under visible light illumination. Abstract : Organic polymer materials, a promising type of photocatalyst, are still restricted by insufficient and poorly distributed active sites. Herein, a series of ultrathin organic polymers with boron as the active site is developed by regulating the B-containing framework. Compared with other monomers, 1, 4-benzenediboronic acid is bonded with hexachlorocyclotriphosphazene to form a compact active site layout in the ultrathin organic polymers (CPB), thus promoting carrier transport and prompting CO2 activation. Without a cocatalyst and photosensitizer, the CPB samples deliver nearly 100% selectivity and a CH4 evolution rate of 1115.8 μmol g −1 (B-free polymer: no activity) under visible light illumination, while maintaining stability (30 h), surpassing many reported photocatalysts. This work provides an efficient way to promote efficient solar energy conversion by weaving metal-free B atoms in a reasonable layout.